1995
DOI: 10.1889/1.1984967
|View full text |Cite
|
Sign up to set email alerts
|

An optically active diffractive device for a high‐efficiency light valve

Abstract: Abstract— A new type of a liquid crystal diffractive light valve, based on optical activity, is proposed. The diffraction results from opposite twisted stripes of nematic liquid crystal material where the twist sense is defined by a patterned alignment layer. The new device demonstrates polarization independent diffraction without the need for high resolution patterning of electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…Because the differently patterned domains require no separation, diffraction efficiency is increased and the risk of shorts between electrodes is reduced. Bos et al [19] have demonstrated the use of pattern alignment with an optically active device for transmissive SLMs. High contrast and relatively low-operation voltage have been demonstrated.…”
Section: Polarization-independent Lc Phase Gratingsmentioning
confidence: 99%
“…Because the differently patterned domains require no separation, diffraction efficiency is increased and the risk of shorts between electrodes is reduced. Bos et al [19] have demonstrated the use of pattern alignment with an optically active device for transmissive SLMs. High contrast and relatively low-operation voltage have been demonstrated.…”
Section: Polarization-independent Lc Phase Gratingsmentioning
confidence: 99%
“…The twist sense is determined according to the tilt direction of the surface LC director so that the elastic free energy takes a minimum value. An LC cell with periodic reverse-twist domains is useful for multidomain TN LC displays 6,7 with symmetric view-ing characteristics and LC gratings 8,9 with polarizationindependent diffraction efficiencies. An alternating distribution of an opposite tilt direction can be formed by a photo alignment method 7 and a multirubbing process 6 using a photolithography.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 To control the electric field at required pixels, the active matrix technique that has been developed for direct view liquid crystal displays can be utilized. However, opaque features of the active matrix limit the maximum transmission of this type of device.…”
mentioning
confidence: 99%
“…2 For the sake of simplicity, this structure is labeled the ''Reverse-Twist'' grating. Similar to the Orthogonal-Twist configuration, it consists of alternating twisted-nematic domains of opposite twist sense and similar surface orientation.…”
mentioning
confidence: 99%
See 1 more Smart Citation